Considerações sobre a inclusão escolar de alunos com necessidades educacionais especiais na educação de jovens e adultos - Parizzi, Roseli Aparecida [UNESP]; Santos, Denise Cristina da Costa França dos (My University, 2011)
This work carried through an exploratory study with nine students with Special Educational Needs (SEN) that had passed for the scholarship in last the ten years and who were registered in the modality of Education for Young people and Adults (EYA). The objective was to identify the effect of the inclusive education, with regard to access and equity in education, in relation to the acquisition of reading, writing and calculation, having as reference the initial cycle of literacy. The research was developed with students aged between 16 and 46 years, in a city in interior of São Paulo (Brazil). About the participants, three were attended the Term I: (1ª and 2ª series), three the Term II (3ª e 4ª series) and three the Term III: (5ª series). An Instrument of Evaluation was elaborated, with specific questions of Portuguese language and mathematics. The study found that in the last ten years, of the investigated group, few students had frequented regular school and those who attended were for a short period of time. The great majority studied, in recent years, only in special school, against the current legislation of inclusive education policy in the Brazilian educational system. Although the students receive the classification of students with SEN, the scholar system demonstrate difficulties in taking care of these students in theirs specific demands of learning and remain, still, the necessity of adequate training of teachers to work in the inclusive schools and to attend the diversity present in the classroom.

Este trabalho realizou um estudo exploratório com nove alunos com Necessidades Educacionais Especiais (NEE) que passaram pela escolaridade nos últimos dez anos e que estavam matriculados na modalidade da Educação de Jovens e Adultos (EJA). O objetivo foi identificar os efeitos da educação inclusiva, no que diz respeito ao acesso e equidade da educação, em relação à aquisição da leitura, escrita e cálculo tendo como referência o ciclo inicial de alfabetização. A pesquisa foi desenvolvida com alunos na faixa etária entre 16 e 46 anos, em uma cidade do interior paulista brasileiro. Dos participantes, três cursavam o Termo I: (1ª e 2ª série), três o Termo II (3ªe 4ª série) e três o Termo III: (5ª série). Elaborou-se um Instrumento de Avaliação, com questões específicas de língua portuguesa e matemática, Constatou-se que nos últimos dez anos, do grupo investigado, poucos alunos freqüentaram o ensino regular e os que freqüentaram foi por pouco tempo. A grande maioria estudou somente em escola especial, contrariando a legislação vigente da política de educação inclusiva no sistema educacional brasileiro. Apesar dos alunos receberem a classificação de alunos com NEE, o sistema escolar demonstra dificuldades em atendê-los em suas demandas específicas de aprendizagem e aponta para a necessidade de formação adequada de professores para atuar em escolas inclusivas e atender a diversidade presente em sala de aula.
Considerations for school inclusion of students with special educational needs in youth and adults
Keywords: EYA; Inclusion; Literacy; Intelectual disabilities; Educational policy; EJA; Inclusão; Alfabetização; Deficiência intelectual; Política educacional